How managerial wage transparency may reduce shareholder returns Evidence from an experiment - Peter Werner; Gary Bolton; Axel Ockenfels (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We study the role of transparency in a novel three-person profit sharing game in which managers and board directors decide on how to distribute the revenues of a company among themselves and shareholders, who are the residual claimants of the companies revenues. We examine two hypotheses. One is that the distribution of revenues is largely determined by an informal quid pro quo among the two decision makers at the expense of shareholders. The second hypothesis is that public transparency attenuates exaggerated manager pay because of increased social pressure. We find strong support for our first hypothesis, but reject the second one: Public transparency actually increases managerial wages as well as board director compensation, further reducing the revenue share that goes to shareholders. Competition to keep managers further magnifies these patterns.
Keywords: C92; G34; D63; 330